Analisis aktivitas fisik, adiksi bermain game online dan status gizi siswa Sekolah Menengah Pertama Negeri 4 dan 18 kota Pontianak - Fikri Akifa Permana; Agustina Arundina Triharja Tejoyuwono; Ita Armyanti (Jurnal Kesehatan Andalas, 2026)
Analysis of physical activity, online gaming addiction, and nutritional status of students at Sekolah Menengah Pertama Negeri 4 and 18 in Pontianak City Adolescent obesity is increasing in line with low physical activity levels and the high prevalence of online gaming. A sedentary lifestyle, such as excessive gaming, may reduce physical activity and negatively affect nutritional status. Objective: To determine the correlation between physical activity and online gaming with nutritional status among students at the junior high schools Sekolah Menengah Pertama Negeri 4 and 18 in Pontianak city. Methods: This research was an observational analytic study with a cross-sectional design. The sample consisted of 190 students selected using purposive sampling. Physical activity was assessed using the PAQ-A questionnaire, online gaming with the GASA questionnaire, and nutritional status by measuring height and weight. Data were analyzed using Spearman’s correlation test. Results: Most students had a moderate level of physical activity (98 students; 51.6%), a moderate frequency of online gaming (125 students; 65.8%), and normal nutritional status (150 students; 78.9%). The analysis showed no significant correlation between physical activity (p = 0.499) or online gaming (p = 0.073) and nutritional status among students at SMPN 4 and 18 Pontianak. Conclusion: Levels of physical activity and online gaming addiction did not significantly affect the nutritional status of early adolescents at Sekolah Menengah Pertama Negeri 4 dan 18 Pontianak. Keywords: physical activity, online games, nutritional status, adolescents, junior high schools